Isolation and characterization of Escherichia coli associated with diarrhea in chickens and ducks in Hai Phong province - Dong, Van Quyen; Pham, Thi Lanh; Nguyen, Kim Oanh (Academia Journal of Biology, 2024)
Colibacillosis is an intestinal tract infection in poultry caused by Escherichia coli. It is one of the leading causes of mortality and results in significant economic losses for the poultry farming sector due to its high incidence rate. Recently, E. coli has been considered a predominant bacterial pathogen that is responsible for diarrhea and bloodstream infections in chickens and ducks in Vietnam. In this study, E. coli strains associated with diarrhea were isolated from chicken and duck feces and intestines collected from poultry farms in Hai Phong province using a Macconkey selective medium. The obtained isolates were initially identified by the MALDI-TOF MS method, screened for hemolytic activity, and finally identified by 16S rRNA gene sequencing. As a result, eight E. coli strains exhibiting hemolytic activity were identified. Among them, E. coli_5, E. coli_6, and E. coli_8 strains were clustered with E. coli O78:H51, whereas E. coli_3 was grouped with E. coli O78:H4; E. coli_4 and E. coli_7 were clusterd with E. coli O25b: H4; and E. coli_9 and E. coli_16 were grouped with E. coli O26:H11. Our results provide insights into the genetic diversity of E. coli strains associated with diarrhea in poultry farms in Hai Phong province. The isolated strains will be further characterized for the development of effective strategies to control colibacillosis in poultry.